Variation in reproductive mode across the latitudinal range of invasive Russian knapweed. Issue 4 (22nd July 2022) - Gaskin, John F; Littlefield, Jeffrey L; Rand, Tatyana A; West, Natalie M
Abstract: For invading species, reproduction is a critical determinant of population establishment as well as spread into new areas. When species have multiple modes of reproduction, the prevalence of different modes can influence management decisions. We used genetic markers to determine the prevalent method of recruitment for invasive Russian knapweed ( Acroptilon repens ). This species forms patches and can spread by both rhizomic growth and seed from outcrossing. We found no shared genotypes between 41 western North American populations, indicating at the macroscale, Russian knapweed is spreading via seed to distant locations. We also examined drivers of reproductive mode by comparing clonality with large-scale environmental factors across the invasion. We found a correlation between latitude and clonal versus seed reproduction, with clonality higher in northern latitude populations. This trend was associated most parsimoniously with decreasing maximum annual temperature and 30-year average of available growing degree days, and increasing soil organic carbon content. These results have management implications: if not properly temporally implemented, grazing or herbicide applications that create open spaces for recruitment may increase the likelihood of Russian knapweed patch persistence through seed, and recently released galling biological control agents in North America may be less effective in northern latitudes where Russian knapweed spread by seed is less prevalent. Abstract : We used genetic markers to determine how invasive Russian knapweed ( Acroptilon repens ) reproduces. This species forms patches and can spread by both root growth and seed. We found no shared genotypes between 41 western North American populations, indicating that Russian knapweed is spreading via seed to distant locations. We found a correlation between latitude and clonal versus seed reproduction, with clonality (spreading by roots) in populations higher in northern latitudes. These results have management implications: if not properly implemented, grazing or herbicide applications that create open spaces for recruitment may increase the likelihood of Russian knapweed patch persistence through seed.